Can China’s ecological civilization strike a balance between economic benefits and green efficiency? A preliminary province-based quasi-natural experiment - Li, Yushan; Liu, Baoliu; Zhao, Pu; Peng, Lin; Luo, Zhilin (Frontiers in Psychology, 2022)
To encourage the building of a development route for ecological civilization construction which commensurates with China's unique national conditions, early demonstration and pilot ecological civilisation zones should be built. This study aims to investigate the effects of ecological civilization pilot construction policies on regional total factor productivity, green total factor productivity, and the methods of action by using panel data from 30 provinces in Mainland China from 2005 to 2020. Our findings indicate that the pilot eco-civilization policies have a more significant effect on the promotion of green total factor production, while the effect on total factor productivity is average. Furthermore, the main purpose of the ecological civilisation construction pilot is to improve the level of green innovation, optimise the industrial structure and promote the allocation of factors to achieve a win-win situation for regional economic development and green benefits. Moreover, under different levels of economic growth, the pilot eco-civilization policies have a more significant effect on the promotion of green total factor at various stages of economic growth and industrialization. There are also clear discrepancies in how well ecological civilisation pilot construction programmes are implemented. Thus, in order to support high-quality regional economic development, it is crucial to continue to advance and promote the pilot eco-civilization initiatives.